Future anxiety mediates the relationship between organ donation and transplantation knowledge and health-related quality of life - Huseynov, Amil; Satici, Begum (BAISHIDENG PUBLISHING GROUP INC, 2025)
BACKGROUND Knowledge about organ donation and transplantation plays a crucial role in shaping individuals' health behaviors and perceptions, potentially impacting their health-related quality of life (HRQoL). Future anxiety, defined as the anticipatory worry individuals experience regarding potential negative events and outcomes in their future, may further influence these outcomes. AIM To investigate the effect of such knowledge on HRQoL and to examine whether future anxiety mediates this relationship. METHODS A cross-sectional study was conducted with 659 participants aged 18 to 65 years. Participants completed the Organ Tissue Donation and Transplantation Knowledge Scale, the Dark Future Scale, and the European Health Interview Survey-Quality of Life 8. Correlation analyses were performed, followed by Structural Equation Modeling to test the proposed mediation model. RESULTS The findings indicated that greater knowledge about organ donation and transplantation was positively associated with higher HRQoL and negatively associated with future anxiety. Future anxiety was negatively correlated with HRQoL. Structural Equation Modeling analysis indicated that knowledge directly enhanced HRQoL and reduced future anxiety. Additionally, future anxiety negatively affected HRQoL, mediating the relationship between knowledge and HRQoL. The mediation effect was significant, as confirmed by bootstrapping (bootstrap coefficient = 0.068, 95%CI: 0.046-0.093). CONCLUSION The study concludes that future anxiety partially mediates the positive impact of knowledge about organ donation and transplantation on HRQoL. These results suggest that increasing public knowledge in this area may reduce future anxieties and enhance quality of life.
Keywords: Health-related quality of life; Organ donation and transplantation; Future anxiety; Structural equation modeling; Mediating; DEPRESSION; Psychiatry